Inheritance of plumage colour in Japanese quails - KHAN, AZMAT ALAM; MISHRA, S K; PRATAP, S O; NARAYAN, RAJ (The Indian Journal of Animal Sciences, 2016)
A complete 4 × 4 diallel cross involving 4 quail populations, 2 of which possessed Pharao, plumage and other 2, White breasted and White plumage pattern was performed and the plumage colour of progeny in different crosses was recorded. The results indicated dominant nature of White breasted and the recessive nature of White feather colour mutations. The inheritance of plumage colours of Pharao, White breasted and White could be explained on the basis of two autosomal plumage color loci.